2022
DOI: 10.1093/bib/bbac432
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning radiomics under multimodality explore association between muscle/fat and metastasis and survival in breast cancer patients

Abstract: Sarcopenia is correlated with poor clinical outcomes in breast cancer (BC) patients. However, there is no precise quantitative study on the correlation between body composition changes and BC metastasis and survival. The present study proposed a deep learning radiomics (DLR) approach to investigate the effects of muscle and fat on distant metastasis and death outcomes in BC patients. Image feature extraction was performed on 4th thoracic vertebra (T4) and 11th thoracic vertebra (T11) on computed tomography (CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…However, their approach constructed imaging features solely from 2D slices of CT images, neglecting the entire tumor. Miao et al [ 18 ] found that combining deep learning with clinicopathological features improved breast cancer prognosis compared to a single modality. Nevertheless, their deep network features were extracted from entire single slices of CT images without region-specific focus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their approach constructed imaging features solely from 2D slices of CT images, neglecting the entire tumor. Miao et al [ 18 ] found that combining deep learning with clinicopathological features improved breast cancer prognosis compared to a single modality. Nevertheless, their deep network features were extracted from entire single slices of CT images without region-specific focus.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its utility, radiomics presents inherent limitations, notably the intricate ROI segmentation process and lack of category representation for hard-coded features. Recent developments underscore the emergence of an innovative paradigm by combining deep learning with radiomics [ 12 , 18 , 19 ]. Deep neural networks directly extract features, providing intricate, category-specific structural insights.…”
Section: Introductionmentioning
confidence: 99%